GLUSTERING ANALYSIS OF MORPHOLOGICAL CHARACTERISTICS OF SIX GENERA OF BRUCHIDAE FAMILY: COLEOPTERA ORDER IN IRAQ - Aead Haj Ismail (Mesopotamia Journal of Agriculture)
The research tackles the taxonomy of six insects genera:Caryedon, Spermophagus, Bruchus, Bruchidius, Callosobruchus and Acanthoselides that belong to Bruchidae family :Coleoptera order which are recorded in Iraq depending on morphological characteristics which were given suitable code for numerical analysis by using clustering analysis statistically packaging SPSS-17. The results were compared by computer to manifest different kinship relations. The results manifest that the relation percentage of phylum is 97% on basis of the degree of similarity of morphological characteristics between Bruchus and Bruchidius genera; and between  Caryedon and Spermophagus genera, whereas the kinship relation between the former two genera and the latter two is 72%, its reveals that  Callosobruchus and Acanthoselides genera have  less degree of relation 27% in this family in Iraq. By using diagrams of  multisided popular relation tree it appears that popular relation of the four  genera Bruchus, Bruchidius,Caryedon and Spermophagus have no kinship relation with the two genera  Callosobruchus and Acanthoselides  i.e. 0%.